The coiled Middle Ordovician cephalopod genera Trocholites and Curtoceras (Tarphyceratida) from Baltoscandia and north-central Europe - Martina Aubrechtová; Dieter Korn (European Journal of Taxonomy)
The family Trocholitidae comprises a diverse group of Middle to Late Ordovician coiled cephalopods known from numerous finds in Baltoscandia and from glacial erratics in the Baltic Sea region. However, most descriptions of these forms date back more than a hundred years. Here we describe 83 specimens of the genera Trocholites and Curtoceras (family Trocholitidae). They were collected from boulders in Pleistocene glacio-fluvial sediments in Germany and Poland, as well as from in-situ strata in Sweden and Estonia. Sixteen species of Trocholites and two species of Curtoceras are identified; twelve species are new: Trocholites baldri sp. nov., T. freyjae sp. nov., T. glacialis sp. nov., T. kadakaensis sp. nov., T. luna sp. nov., T. splendor sp. nov., T. triangulus sp. nov., T. tureki sp. nov., T. vodickai sp. nov., T. vortex sp. nov., T. zaryensis sp. nov. and Curtoceras meyeri sp. nov. The diagnoses of previously described taxa are revised by incorporating information on ontogenetic changes, ontogenetic trajectories and variation of morphological characters. The three species of Trocholites established by Eichwald (1840), T. odini, T. incongruus and T. depressus, are synonymised and the latter name is retained based on priority. Neotypes are proposed for Trocholites depressus, T. macrostoma and T. contractus. Curtoceras estonicum Balashov, 1953 is synonymised with C. teres. Trocholites macromphalus Schröder, 1891 and Trocholites scoticus Blake, 1882 are transferred to Curtoceras. The species names soraviensis and orbis are considered valid but are still not used in this work because the original type collection was probably destroyed during World War II and no other specimens could be reliably assigned to any of these taxa.